Spirit of Liberation and Justice in Farid Esack’s Hermeneutics of Qur’an - Erik Sabti Rahmawati (Universitas Islam Negeri Mataram, 2016)
Farid Esack is an Islamic thinker from South Africa who proposes Liberation hermeneutics in comprehending the Qur’an from the perspective of Liberation Theology to realize justice. This article examines Esack’s hermeneutical method in interpreting Qur’an and analyses how he applies the spirit of liberation and justice as principles of Liberation Theology in his interpretation. This study shows that Esack’s hermeneutics differs from others because, as a liberation theologian, he puts liberative-praxis as the main objective of his liberation theology. His method does not only revolve around textual understanding but also push practical implication. He moves forward from praxis (experience) to texts and then goes back to experience. To him, interpretation must be able to encourage changes within society. Therefore, as the second feature of this method, in Esack’s hermeneutics, interpretation is not just scholarly speculative exercise which has no implication. It has a specific aim, namely is to establish a better life for society in which justice is a fundamental prerequisite. DOI: http://dx.doi.org/10.20414/ujis.v20i1.822